Marine biochemistry : applications - Kim, Se-Kwon (London CRC Press, 2023)
"This 2 volume set discusses the functions, metabolism and composition, biochemistry, illuminate materials, of fish and shellfish. It explores the utilization of byproducts from marine sources and explains the basic level implications in the development and application of marine biochemistry"--
v. 1. Isolations and techniques -- v. 2. Applications.
Includes bibliographical references and index.
Keywords: Marine biotechnology; Marine animals; Marine animals; Biochemistry; Marine biology